Forecasting the 2015 British general election: The Seats-Votes model. (March 2016) - Whiteley, Paul; Clarke, Harold D.; Sanders, David; Stewart, Marianne C.
Abstract: This paper applies the Seats-Votes Model to the task of forecasting the outcome of the 2015 election in Britain in terms of the seats won by the three major parties. The model derives originally from the 'Law of Cubic Proportions' the first formal statistical election forecasting model to be developed in Britain. It is an aggregate model which utilises the seats won by the major parties in the previous general election together with vote intentions six months prior to the general election to forecast seats. The model was reasonably successful in forecasting the 2005 and 2010 general elections, but has to be modified to take into account the 'regime shift' which occurred when the Liberal Democrats went into coalition with the Conservatives in 2010. Highlights: A modified 'Cube Rule' is used to forecast seats won in the 2015 election based on data from 1945 to 2010. The model predicted a hung Parliament with no party having an overall majority of seats, a predictive failure. We show that part of the predictive failure was due to the fact that the poll data did not capture the vote intentions of those who actually participated in the election. We also show that the Coalition government represented a 'regime shift' in the time series and adjustments for this using an ARIMA model were sufficient to capture the Liberal Democrat seat share providing the party's seat shares in the 2010 Parliament were ignored.